Diabetes Mellitus Screening Through Blood Sugar Checks in the Elderly - Arafah, Salmah; Kamriana, Kamriana (PABBURA : Health Service Journal, 2024)
Background: Diabetes mellitus (DM) is a non-communicable disease characterized by blood sugar levels that exceed normal. An easy way to detect whether there is the potential for diabetes is by checking blood sugar levels. Objective: This activity aims to carry out DM screening through checking blood glucose levels and consulting blood sugar results while at the mosque, Manongkoki Village, Takalar Regency. Method: The target of this activity is the elderly, numbering 37 people. The implementation time is Monday, February 13 2023. Activities include a temporary blood sugar check (GDS) followed by a consultation on blood sugar results. Results: A total of 37 elderly people who participated in this activity were mostly women (73%), men (27%). From the results of the GDS examination, the average GDS level was 142.12 gr/dl. Elderly people who do not suffer from DM (76%). Conclusion: Most elderly people have normal GDS levels. However, early detection efforts still need to be made so that Diabetes Mellitus complications do not occur.